Genetic Analysis of CYP2C9 with Reference to Drug Response in Epilepsy Patients of Pakistan - Hafsa Maqbool; Tayyaba Saleem; Nadeem Sheikh; Aqsa Ashfaq (Genetics Research)
Epilepsy is a major global issue. Epilepsy patients are treated with AED (antiepileptic drugs). Interindividual variability in drug response has been documented in several studies. The resistance to drug response may be attributed to genetic polymorphism. The current study was undertaken to investigate the CYP2C9 gene polymorphism associated with antiepileptic drug (AED) resistance in the Pakistani population. The current study included 337 individuals including 100 control subjects, 110 drug-resistant subjects, and 127 drug responders. Genomic DNA was isolated from blood, and amplification of rs1799853 (430C > T) and rs1057910 was carried out by polymerase chain reaction. Genotypes of CYP2C9 SNPs were determined by Sanger’s sequencing. Astounding results were observed in the current study that none of the well-known reported SNPs of CYP2C9 was found in our Pakistani cohorts. However, a novel missense variant (c.374G > A) was found only in drug-resistant patients of the current study. According to the in silico analysis performed by PolyPhen-2, it was observed that this nonsynonymous substitution is likely to be pathogenic. The results of our study demonstrated that rs1799853 and rs1057910 may be involved in drug resistance in the Pakistani population. However, some other variants on CYP2C9 may play a critical role in AED resistance that needs to be explored.